All sub‐nanosecond laser monolithic interconnection of OPV modules. (27th February 2019) - Kubis, Peter; Winter, Jan; Gavrilova, Anna; Hennel, Markus; Schlosser, Susanne; Richter, Isabel; Distler, Andreas; Heyder, Madeleine; Kery, Stefan; Lenk, Peter; Geiger, Stephan; Brabec, Christoph J.; et al.
Abstract: Although green femtosecond lasers provide outstanding quality and wide processing windows for monolithic interconnection of the individual cells in organic photovoltaic (OPV) modules, they are hardly used in commercial applications, due to cost reasons. In this work, a process has been developed that allows the monolithic interconnection in OPV modules with an infrared sub‐nanosecond laser exclusively, without compromising the performance of the modules. While the photoactive layer is removed easily by green femtosecond pulses without damaging the bottom electrode, this is not possible for infrared nanosecond pulses, due to their much larger optical penetration length, which significantly exceeds the thickness of the active layer and is well absorbed by the indium tin oxide (ITO) layer. This leads to damage of the ITO bottom electrode, which in turn compromises the functionality of the module. By systematically varying single‐pulse laser fluence and spatial pulse overlap, the laser parameters are optimized in such a way that the contact area between the residues of the metal oxide bottom electrode and the silver nanowire top electrode is maximized so that the electrical resistances of the contacts are sufficiently small not to affect device performance. This is demonstrated by presenting large‐area OPV modules based on the well‐characterized reference system P3HT:PCBM that show efficiencies of up to 2.4%. This achievement opens up the way towards reliable roll‐to‐roll (R2R) laser patterning processes with sub‐nanosecond lasers and thus represents a breakthrough with respect to cost‐effective R2R manufacturing of OPV modules, due to grossly reduced investment and maintenance costs for laser sources. Abstract : In this work, a process has been developed that allows the monolithic interconnection in organic photovoltaic (OPV) modules with an infrared sub‐nanosecond laser exclusively, without compromising the performance of the modules. This achievement opens up the way towards reliable roll‐to‐roll (R2R) laser patterning processes with sub‐nanosecond lasers and thus represents a breakthrough with respect to cost‐effective R2R manufacturing of OPV modules, due to grossly reduced investment and maintenance costs for laser sources.